Age-related psychometrics and differences in gratitude and future time perspective across adulthood. (November 2021) - Allemand, Mathias; Olaru, Gabriel; Hill, Patrick L.
Abstract: The current study examined age-related psychometrics and differences in the measurement, mean-levels, variances, and correlations of gratitude and future time perspective across adulthood using data from a cross-sectional survey in a representative Swiss sample ( N = 1684, age range: 19–98 years). Local structural equation modeling was used to investigate these measurement parameters based on age as a continuous variable instead of using artificial age groupings. After having established a measurement model with three interrelated factors of gratitude, opportunities and time, results indicate that the measurement model demonstrates at least metric measurement invariance for all factors. Gratitude mean-levels and correlations with future time perspective remained stable across the examined age range. We did find a strong decline in perceived remaining opportunities and time across age, and an increase in the variance of these constructs. This suggests that people generally perceive time and opportunities as more limited with increasing age, but that the interindividual differences in this perception are particularly large in old age.